(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The present study summarizes the achievements of the polish researchers about the socio-cultural phenomenon of martial arts, shown from the historical perspective of these practices in Poland and the long-time tradition of local martial practices, as well as from the author’s thirty-year of practice and research in martial arts field. The main directions of the multidisciplinary, sociological, historical and pedagogical research are considered, in addition to the institutionalization of scientific activities related to the martial arts such as the organization of periodic conferences and the publication of specific journals. Particularly, the achievements of the Rzeszów’s Research Center, which is becoming an international cornerstone in the scientific study of the martial arts, are detailed.